IMPROVING COMMUNITY HEALTH THROUGH HEALTH SCREENING FOR POSYANDU CADRES AND THE COMMUNITY OF JAYARAGA VILLAGE - Andhika Lungguh Perceka Andhika Lungguh Perceka; Hasbi Taobah Ramdani Hasbi Taobah Ramdani; N. Ai Erlinawati N. Ai Erlinawati; Herlin Rusyani Herlin Rusyan; Sugiah Sugiah; Gina Mutmainna Gina Mutmainna; Wieda Widyatry Qarragita Wieda Widyatry Qarragita; Dani Sujana Dani Sujana; Yogi Rahman Nugraha Yogi Rahman Nugraha (Jurnal Pengabdian Masyarakat DEDIKASI, 2025)
This Community Service Activity (PkM) aims to identify risk factors for diabetes mellitus (DM) as one of the comorbidities that exacerbate the condition of the elderly. The expected outcome of this activity is for residents to be aware of the risk factors for the disease and their own health conditions, particularly regarding DM. It is hoped that this activity will increase community awareness about DM management. The activity was attended by 50 residents of Jayaraga Village, Tarogong Kidul District, Garut Regency. The results of the activity revealed that 7 individuals (14%) confirmed having diabetes mellitus, 31 individuals (62%) had hypertension, and 12 individuals (24%) had gout. Therefore, through this community service initiative, we conducted a health screening program that included free blood pressure checks, uric acid tests, and blood sugar level measurements, as well as weight checks and health education, particularly on diabetes and its prevention methods. With the implementation of this community service initiative, we hope that the health-related issues in Jayaraga Village, Tarogong Kidul Sub-district, Garut Regency, can be addressed to some extent.